Transparent ternary alloy counter electrodes for high-efficiency bifacial dye-sensitized solar cells. (August 2018) - Liu, Tianshu; Zhao, Yuanyuan; Duan, Jialong; He, Benlin; Zheng, Jingjing; Tang, Qunwei
Graphical abstract: Highlights: Bifacial DSSC is developed to harvest solar energy from front and rear sides. Transparent ternary (CoM)0.85 Se alloy CEs are synthesized by a hydrothermal method. The alloy CEs have high optical transparency and catalytic activity. The bifacial DSSC yields a front efficiency of 9.14% and rear efficiency of 3.86%. Abstract: Bifacial dye-sensitized solar cells (DSSCs) are regarded as promising photovoltaics to harvest solar energy from both front and rear sides because of their significantly increased total power outputs. Transparent counter electrodes (CEs) with cost-effectiveness and high electrocatalytic activity are crucial to make these high-performance bifacial devices. Herein, a category of transparent CEs from ternary alloys [(CoM)0.85 Se, M = Ni, Ru, Fe] are synthesized by a mild solution method. Upon careful optimization on optical behaviors, electrocatalytic activity and photovoltaic performances, the bifacial DSSCs with (CoNi)0.85 Se, (CoRu)0.85 Se, (CoFe)0.85 Se CEs achieve front power conversion efficiencies of 9.14%, 8.09%, 7.58% and rear efficiencies of 3.86%, 3.31%, 3.51% in comparison with 6.72% and 3.16% for state-of-the-art Pt CE based solar cell, respectively. Moreover, these bifacial DSSCs devices display high multiple on/off capability and relatively good stability.